Regulation of positive and negative emotion: effects of sociocultural context - Snyder, Sara A.; Heller, S. Megan; Lumian, Daniel S.; McRae, Kateri (Frontiers in Psychology, 2013)
Previous research has demonstrated that the use of emotion regulation strategies can vary by sociocultural context. In a previous study, we reported changes in the use of two different emotion regulation strategies at an annual alternative cultural event, Burning Man (McRae, Heller, John, & Gross, 2011). In this sociocultural context, as compared to home, participants reported less use of expressive suppression (a strategy generally associated with maladaptive outcomes), and greater use of cognitive reappraisal (a strategy associated with adaptive outcomes). What remained unclear was whether these changes in self-reported emotion regulation strategy use were characterized by changes in the regulation of positive emotion, negative emotion, or both. We addressed this issue in the current study by asking Burning Man participants separate questions about positive and negative emotion. Using multiple datasets, we not only replicated our previous findings, but also found that the decreased use of suppression is primarily driven by reports of decreased suppression of positive emotion at Burning Man. By contrast, the reported increased use of reappraisal is not characterized by differential reappraisal of positive and negative emotion at Burning Man. Moreover, we observed novel individual differences in the magnitude of these effects. The contextual changes in self-reported suppression that we report are strongest for men and younger participants. For those who had previously attended Burning Man, we observed lower levels of self-reported suppression in both sociocultural contexts: Burning Man and home. These findings have implications for understanding the ways in which certain sociocultural contexts may decrease suppression, and possibly minimize its associated maladaptive effects.